Excessive gestational weight gain, food insecurity and its associated factors among pregnant women in antenatal clinic, Hospital Universiti Sains Malaysia - Abdullah, Haniff (2015)
Nutrition during the pregnancy period is important as adequate nutrients are necessary for foetal development and prevention of future adult disease development, thus food insecurity is a public health problem that affect maternal, child and later adult health. The objective of this study was to identify the prevalence of household food insecurity among pregnant women who attended antenatal clinic, Hospital Universiti Sains Malaysia, Kota Bharu and also to determine the association between food insecurity and gestational weight gain. This cross sectional study used the Radimer/Cornell Hunger and Food Insecurity Instrument as an assessment tool for food security. A total of 235 pregnant women participated in the study. The prevalence of food insecurity among pregnant women household was 41.3%; consisting of, in categories of severity, 32.3% household food insecure, 0.9% individual food insecure and 8.1% child hunger. The mean gestational weight gain of the participants was 8.8 kg (SD 5.05). This study found that food insecurity was significantly associated (χ2= 10.98, p= 0.004) with gestational weight gain. The Multiple Logistic Regression, with excessive pregnancy weight gain as outcome, showed pregnant women who had food insecurity were 4.8 times (adjOR 4.80, 95% CI: 1.94, 11.86; p=0.001) more likely to have excessive gestational weight gain compared to the food secured pregnant women. Being overweight and obese at pre-pregnancy was at higher odds (adjOR6.17, 95%CI: 2.70, 14.09; p<0.001) of excessive gestational weight gain compared to women with normal body mass index prior to pregnancy. The study found that there were significant association between food insecurity and high pre-pregnancy body mass index with gestational weight gain in the antenatal clinic, Hospital Universiti Sains Malaysia, Kota Bharu. Therefore, there is a need to ensure adequacy of food and nutrients among pregnant women.